INNOVATIONS IN ENVIRONMENTAL LEGISLATION AS A THREAT TO BIODIVERSITY CONSERVATION - ZLOTNIKOVA Tamara Vladimirovna (Правовое государство: теория и практика)
One of the tasks of national environmental legislation at the present stage is legal regulation of specially protected natural areas (hereinafter – SPNA), whose contribution to biodiversity conservation can hardly be overestimated. The article considers changes in the legislation on SPNA and related problems of functioning of such areas. The article shows how innovations with serious weakening of the protective and conservation regime for different categories of SPNA are becoming increasingly dangerous for the implementation of the main function for which the protected area system of the country is created, i.e., for the purpose of biodiversity conservation. Particular attention is paid to changes in «reserved area» legislation related to the development of tourism within the boundaries of such territories. Purpose: to analyse changes in environmental legislation, including the legislation on SPNA and wildlife, affecting biodiversity conservation, and to develop proposals to reduce such impacts. Methods: empirical methods of comparison and description, theoretical methods of formal and dialectical logic; specific scientific methods: juridical-dogmatic and interpretation of legal norms. Results: the article develops some pr oposals to change the legislation on SPNA, aimed at minimising damage to natural complexes and biodiversity conservation when developing tourism in specially protected areas. In particular, the article proposes to enshrine in the Federal Law «On specially protected natural areas» the concept of geopark as a new category of regional SPNA, to specify the concepts of «ecological tourism» and «educational tourism» as types of tourist activities allowed in SPNA, as well as to enshrine the mandatory construction of capital recreational and tourist infrastructure facilities exclusively in protected areas of SPNA, and in the case of tourism development in SPNA – the advanced organisation of protection zones where they are not y et provided.